Heat Shock Protein 70 Regulates Degradation of the Mumps Virus Phosphoprotein via the Ubiquitin-Proteasome Pathway - Katoh, Hiroshi (J Virol, 2014)
Mumps virus (MuV) infection induces formation of cytoplasmic inclusion bodies (IBs). Growing evidence indicates that IBs are the sites where RNA viruses synthesize their viral RNA. However, in the case of MuV infection, little is known about the viral and cellular compositions and biological functions of the IBs. In this study, pulldown purification and N-terminal amino acid sequencing revealed that stress-inducible heat shock protein 70 (Hsp72) was a binding partner of MuV phosphoprotein (P protein), which was an essential component of the IB formation. Immunofluorescence and immunoblotting analyses revealed that Hsp72 was colocalized with the P protein in the IBs, and its expression was increased during MuV infection. Knockdown of Hsp72 using small interfering RNAs (siRNAs) had little, if any, effect on viral propagation in cultured cells. Knockdown of Hsp72 caused accumulation of ubiquitinated P protein and delayed P protein degradation. These results show that Hsp72 is recruited to IBs and regulates the degradation of MuV P protein through the ubiquitin-proteasome pathway. IMPORTANCE Formation of cytoplasmic inclusion bodies (IBs) is a common characteristic feature in mononegavirus infections. IBs are considered to be the sites of viral RNA replication and transcription. However, there have been few studies focused on host factors recruited to the IBs and their biological functions. Here, we identified stress-inducible heat shock protein 70 (Hsp72) as the first cellular partner of mumps virus (MuV) phosphoprotein (P protein), which is an essential component of the IBs and is involved in viral RNA replication/transcription. We found that the Hsp72 mobilized to the IBs promoted degradation of the MuV P protein through the ubiquitin-proteasome pathway. Our data provide new insight into the role played by IBs in mononegavirus infection.